2013
DOI: 10.1038/nrneph.2013.58
|View full text |Cite
|
Sign up to set email alerts
|

Renal albumin filtration: alternative models to the standard physical barriers

Abstract: Human kidneys produce more than 4 million litres of virtually protein-free primary urine in a lifetime. In healthy individuals, the sieving process is accomplished by the glomerular filter without the smallest sign of clogging, even in old age. How nature accomplishes this extraordinary task is a mystery, but unravelling the functioning of the glomerular filter is important. The basic principles that govern glomerular filtration are probably also true for peripheral filtering by fenestrated capillaries. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 66 publications
1
43
0
Order By: Relevance
“…21,22 In addition, we have used an expansion of this model, which also considers electrical effects. [23][24][25] This electrokinetic model proposes that an electrical field is generated across the glomerular filter by forced filtration of the small ions (e.g., sodium and chloride), which pass the filter at different speeds because of physical interactions with the charged filter surface ( Figure 1B). 25 Recently, this streaming potential has been experimentally verified by direct measurements.…”
Section: Mathematical Modeling Of Glomerular Backfiltration Of Albuminmentioning
confidence: 99%
“…21,22 In addition, we have used an expansion of this model, which also considers electrical effects. [23][24][25] This electrokinetic model proposes that an electrical field is generated across the glomerular filter by forced filtration of the small ions (e.g., sodium and chloride), which pass the filter at different speeds because of physical interactions with the charged filter surface ( Figure 1B). 25 Recently, this streaming potential has been experimentally verified by direct measurements.…”
Section: Mathematical Modeling Of Glomerular Backfiltration Of Albuminmentioning
confidence: 99%
“…Nephrol. 9, 266-277; 2013) 1 and the others in the Nature Reviews Nephrology collection, which raises two important issues that must be addressed (Albuminuria is controlled primarily by proximal tubules. Nat.…”
Section: Correspondencementioning
confidence: 99%
“…3,4 Several lines of evidence support this position. 1,3 For example, micropuncture studies in the rat kidney have demonstrated very low albumin concentrations in the primary filtrate. In cooled or fixed isolated perfused kidney, cubilin/megalin knockout mice or human patients with Fanconi syndrome, only very little protein is excreted in the urine (<1 g albumin per day in humans).…”
Section: Correspondencementioning
confidence: 99%
See 2 more Smart Citations